Terror : Australia - Australia's response to post-modern terrorism. - Wayne Werner Robert Buchhorn. (2008)
Examine the Australian response to the terrorism by assessing the level of threat from universal Islamic radical ideology and reviewing the suite of legislative and bureaucratic changes implemented by the Australian Government and look at the efficacy of those changes.